Rare variants in PLD3 do not affect risk for early-onset Alzheimer disease in a european consortium cohort - Cacace, Rita (2015)
© 2015 The Authors. ∗∗ Human Mutation published by Wiley Periodicals, Inc. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.